Analysis of the Effectiveness of the Indonesian Men’s National Volleyball Team’s Attacks at the 2025 SEA Games - M. Rizal As'ad Riyadi; Wiga Nurlatifa Romadhoni (Journal of Physical Education Health and Sport, 2026)
Modern volleyball is heavily influenced by the effectiveness of attacking techniques, as attacks are the primary strategy for scoring points and determining the outcome of a match. Therefore, analysing the effectiveness of various types of attacks is crucial for evaluating a team’s performance in a match. The objective of this study is to provide information about the most effective attacks used bye the Indonesian Men’s National Volleyball Team at the 33rd SEA Games in 2025 in Thailand. This study uses a quantitative approach, descriptive research type, where data collection techniques use non-participant observation, as well as secondary data sources obtained through videos from the MNCTV Sports YouTube channel, consisting of 4 videos of the 33rd SEA Games 2025 in Thailand. The research instrument uses a statistical form for open attack, quick attack, back attack, and service attack. The data analysis technique used descriptive percentages. The results of the study show that the most effective attacks are as follows: open attack has an attack effectiveness rate of 54.17%, quick attack has an attack effectiveness rate of 60.61%, back attack has an attack effectiveness rate of 55.79%, and service attack has an attack effectiveness rate of 3.91%. The conclusion of this study states that the most effective attacks used by the Indonesian Men’s National Volleyball Team at the 33rd SEA Games in 2025 in Thailand are quick attacks in first place, back attacks in second place, open attacks in third place, and service attacks in fourth place.